AUTOMATION OF TAX ADMINISTRATION: CHALLENGES AND DEVELOPMENT PROSPECTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the issues of automating tax administration and its role in improving the efficiency of the tax system in the context of digital transformation. The automation of tax administration is considered one of the key tools for increasing tax collection efficiency, reducing administrative costs, minimizing the shadow economy, and enhancing transparency between tax authorities and taxpayers. The paper analyzes the economic essence of tax administration, the main directions and stages of its automation, modern information and communication technologies used in tax systems, and international best practices. In addition, the article identifies the main challenges faced in the automation process, including technological, institutional, legal, and human resource-related problems. Special attention is given to the experience and prospects of tax administration automation in developing economies, with recommendations aimed at improving digital tax governance and ensuring sustainable fiscal development.